The Effect of Organizational Support on Organizational Citizenship Behavior Mediated By Organizational Commitment - Ni Ketut Rika Harum Sari; Ida Bagus Ketut Surya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of organizational support on organizational citizenship behavior with organizational commitment as a mediating variable. The sample consisted of 43 respondents selected using a saturated sampling (census) method. Data were collected through questionnaires and analyzed using descriptive statistics and inferential analysis through the Partial Least Squares Structural Equation Modeling (SEM-PLS) approach. The results indicate that organizational support has a positive and significant effect on organizational citizenship behavior. Organizational commitment also has a positive and significant effect on organizational citizenship behavior. Furthermore, organizational support positively and significantly affects organizational commitment. Organizational commitment partially and complementarily mediates the influence of organizational support on organizational citizenship behavior. Theoretically, this research supports the Social Exchange Theory. Practically, the findings can serve as input for the management of Taman Tirtagangga to enhance employee support in order to foster voluntary behaviors and employee commitment.